2018
DOI: 10.20944/preprints201806.0221.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of Emotional Intelligence in Engagement in Nurses

Abstract: 1) Background: Aware that engagement in the healthcare field needs high levels of emotional intelligence, we began this study in to the relationship between engagement and emotional intelligence in nurses. The objective of this study was to determine the explanatory value of the components of emotional intelligence for engagement in a sample of nurses, and to identify which of the emotional intelligence components have the greatest explanatory value for dimensions of engagement, by sex.; 2) Methods: The final … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
2
0
0
Order By: Relevance
“…Moreover, the present study showed that psychiatric nurses with the ability to empathize (OEA) tend to possess higher work engagement. This finding is similar to that presented in a previous study wherein a positive relationship was found between the interpersonal dimension, including empathy of emotional intelligence, and work engagement among nonpsychiatric nurses (Pérez‐Fuentes, Molero Jurado, Gázquez Linares, & Oropesa Ruiz, ). Empathy has been considered to cultivate a deeper interpersonal relationship between psychiatric patients and nurses (Delaney, Shattell, & Johnson, ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the present study showed that psychiatric nurses with the ability to empathize (OEA) tend to possess higher work engagement. This finding is similar to that presented in a previous study wherein a positive relationship was found between the interpersonal dimension, including empathy of emotional intelligence, and work engagement among nonpsychiatric nurses (Pérez‐Fuentes, Molero Jurado, Gázquez Linares, & Oropesa Ruiz, ). Empathy has been considered to cultivate a deeper interpersonal relationship between psychiatric patients and nurses (Delaney, Shattell, & Johnson, ).…”
Section: Discussionsupporting
confidence: 91%
“…Emotionally intelligent nurse managers are better equipped with ways and manners of dealing with workplace disagreement and stress (17,18), helping to reduce burnout and stress management which is a major cause of workrelated challenges such as conflict (19) which supported the findings of this new study establishing that, nurse managers manifest their emotions by their ability to combine their emotional intelligence to their leadership style in managing conflicts (15). Emotionally intelligent nurse managers are very attentive to the emotions of others, therefore, controlling their emotions and easily coping with the demands of subordinates (4,20,21). However, most health care practitioners such as nurses in the United Kingdom have been criticized for their inability to accommodate such pressure from patients and co-workers which has resulted in negative health consequences for patients.…”
Section: Discussionsupporting
confidence: 52%